Rubble & crew [videorecording (DVD)]. (Paramount Home Entertainment, 2023)
Welcome to Builder Cove, a friendly town where there's always something to build, repair, maintain, paint, and construct. This small yet quickly growing community already has plenty of shops, homes, and Main Street buildings, but it still needs a bigger airport, train station, bridges, tunnels, schools, fire stations, parks, and much more. And that's where Rubble and his pup family come in! With Rubble leading the way as the foreman, the whole family is part of a construction team called "Rubble & Crew!" Together they work hard to build whatever the town of Builder Cove needs. Let's bow-wow build!